Dietary ratio of animal:plant protein is associated with 24-h urinary iodine excretion in healthy school children. Issue 1 (10th June 2015) - Montenegro-Bethancourt, Gabriela; Johner, Simone A.; Stehle, Peter; Remer, Thomas
Abstract : Adequate dietary iodine intake in children is essential for optimal physical and neurological development. Whether lower dietary animal food and salt intake may adversely affect iodine status is under discussion. We examined the association between dietary animal:plant protein ratio with 24-h urinary iodine excretion (24-h UI, μg/d), and whether this is modified by salt intake. A 24-h UI was measured in 1959 24-h urine samples from 516 6- to 12-year-old participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study. Parallel 3 d weighed food records were used to estimate dietary intakes. Protein sources were classified as dairy, animal and plant. A repeated-measures regression model (PROC MIXED) was used to analyse the effect of animal:plant protein ratios on 24-h UI. Animal:plant protein ratios ranged from 0·5 (95 % CI 0·4, 0·6) to 1·6 (95 % CI 1·4, 1·9) (lowest and highest quartile). After adjustment for total energy intake, main dietary iodine sources (dairy and salt intake), and further covariates, the inter-individual variation in animal:plant protein ratio was significantly associated with variation in 24-h UI. One unit higher animal:plant protein ratio predicted 6 μg/d higher 24-h UI ( P = 0·002) in boys and 5 μg/d ( P = 0·03) in girls. This relationship was partially mediated by a higher salt intake at higher animal:plant protein ratios. These results suggest that lower consumption of animal protein is associated with a small decline in iodine excretion, partially mediated by decreased salt intake. Because limited salt and increased intake of plant-based foods are part of a preferable healthy food pattern, effective nutrition political strategies will be required in the future to ensure appropriate iodine nutrition in adherent populations.